Anatomical and radiological studies of human coracoid process in Selangor, Malaysia - Taher, Manal Fathi A.M. (2017)
There is scarcity in the literature concerning the anatomy and radiology study of human coracoid process in the diverse Asian population. This research was undertaken to investigate the anatomy of the coracoid process through developing a new dissection approach to access the coracoid process of the human scapula and quantifying the coracoid process morphometry among Indian, Chinese, and Myanmar subjects. This research further investigates the radiology of the coracoid process via quantifying the morphometry and the regional bone mineral density of the coracoid process among Malay and Chinese subjects.